EVALUATING THE EMPLOYEE WELFARE PROGRAM AT PT. TIRTA INVESTAMA (DANONE AQUA) AIRMADIDI BY USING THE IMPORTANCE AND PERFORMANCE ANALYSIS - Manengkey, Cheryl .; Saerang, David P.E; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Company and employee are two elements that cannot be separated. Without the employees, the company will not be able to perform to achieve its goals. On the other hand, the employees will not be able to support their welfare without the company as a place to work and make a living. One of the strategies that the company can do to manage the employee performance is by giving the employee a proper welfare program which can support the employee performance. The objectives in this research is to know importance and performance of employee welfare program in PT Tirta Investama (Danone AQUA) Airmadidi. Results based on Importance Performance Analysis, which are: National security for the workforce (JAMSOSTEK/BPJS) Membership and Economic enterprise are located in quadrant I â€œconcentrate hereâ€ (high importance, low performance), Outside workplace accident insurance, Life insurance, Place of worship and Recreation are located in quadrant II â€œkeep up the good workâ€ (high importance, high performance), Sport & Art are located in quadrant III â€œlow priorityâ€ (low importance, low performance). There is no program that located in quadrant IV â€œpossible overkillâ€ (low importance, high performance).Keywords: importance and performance analysis, employee welfare